The war between SingTel and M1. - Loh, Jessica Pui See. (2008)
The aim of this study is to examine the marketing strategies of two mobile service providers -- SingTel Mobile and MobileOne (M1). Interviews with the management and staff of the two companies are carried out and surveys are also conducted to find out consumers' perceptions of the two companies. Different types of questionnaires are designed to cater to users of the SingTel GSM900, SingTel GSM1800, M1 GSM900 and M1 CDMA. Additionally, the opinions of non-users are also included in the survey.